Comparison of Conventionally Measured Serum Bicarbonate Values with Bicarbonate Values Obtained in Arterial and Venous Blood Gas Analysis (Bangladesh Journal of Medical Biochemistry, 2013)
Bicarbonate (HCO3-) measurement in serum or plasma from a sample of venous blood is routinely practiced in hospital patient management. HCO3- status can also be assumed from Blood gas analysis requiring arterial blood as sample which is cumbersome for both patients and doctors. This study was undertaken to evaluate the extent of agreement among biocarbonate values obtained during venous, arterial blood gas analysis and conventionally measured serum bicarbonate levels in a group of intensive care unit (ICU) patients to determine whether conventionally measured serum HCO3- (from peripheral venous blood) and calculated HCO3-values (from arterial blood gas [ABG] analyzers) can be used interchangeably. A total of 51 adult patients with diverse medical conditions, presenting at a tertiary health centre ICU were enrolled in this study when deemed by the treating physician to have an ABG analysis. Arterial and venous samples were taken as close in time as possible for blood gas analysis and routine blood tests. Bland-Altman analyses were used to compare the three methods. The HCO3- levels from ABG, Venous Blood gas (VBG) and tconventionally measured serum HCO3- showed acceptably narrow 95% limits of agreement using the Bland-Altman method. VBG reveals higher level of agreement with the ABG bicarbonate values compared to measured serum HCO3-. Thus, venous blood can be an alternate for arterial blood where ABG analyzer is available. conventionaly serum HCO3- measurements can also be useful and used as substitute for an expensive ABG analyzer in resource constrained health care sectors when required. DOI: http://dx.doi.org/10.3329/bjmb.v5i1.13425 Bangladesh J Med Biochem 2012; 5(1): 12-15